Marathon Kids UK: study design and protocol for a mixed methods evaluation of a school-based running programme. Issue 5 (14th May 2018) - Chalkley, Anna E; Routen, Ash C; Harris, Jo P; Cale, Lorraine A; Gorely, Trish; Sherar, Lauren B
Abstract : Introduction: Schools are promising settings for physical activity promotion; however, they are complex and adaptive systems that can influence the quality of programme implementation. This paper presents an evaluation of a school-based running programme (Marathon Kids). The aims of this study are (1) to identify the processes by which schools implement the programme, (2) identify and explain the contextual factors affecting implementation and explications of effectiveness and (3) examine the relationship between the level of implementation and perceived outcomes. Methods: Using a realist evaluation framework, a mixed method single-group before-and-after design, strengthened by multiple interim measurements, will be used. Year 5 (9–10 years old) pupils and their teachers will be recruited from six state-funded primary schools in Leicestershire, UK. Data will be collected once prior to implementation, at five discrete time points during implementation and twice following implementation. A weekly implementation log will also be used. At time point 1 (TP1) (September 2016), data on school environment, teacher and pupil characteristics will be collected. At TP1 and TP6 (July 2017), accelerometry, pupil self-reported physical activity and psychosocial data (eg, social support and intention to be active) will be collected. At TP2, TP3 and TP5 (January, March and June 2017), observations will be conducted. At TP2 and TP5, there will be teacher interviews and pupil focus groups. Follow-up teacher interviews will be conducted at TP7 and TP8 (October 2017 and March 2018) and pupil focus group at TP8. In addition, synthesised member checking will be conducted (June 2018) with a mixed sample of schools. Ethics and dissemination: Ethical approval for this study was obtained through Loughborough University Human Participants Ethics Subcommittee (R16-P032 & R16-P116). Findings will be disseminated via print, online media and dissemination events as well as practitioner and/or research journals.